MANAGING THE ECO-ENVIRONMENTAL COST AND FIRMS PERFORMANCE IN NIGERIA: THE PUBLIC CONSUMER GOODS FIRMS IN PERSPECTIVE (Journal of Contemporary Issues in Accounting, 2026)
This study evaluated how the management of listed consumer goods firm’s eco environmental cost affects its performance in Nigeria. Utilising extracts from the audited financial statements of 16 firms sampled from a population of 21 consumer goods firms listed on the Nigerian Exchange Group for the period 2012 – 2023, the study specifically ascertained the effect of Employee Health and Safety Disclosure (EHSD), Pollution Control Disclosure (PCD) and Environmental Remediation Disclosure (ERD), on return on capital employed (ROCE) of these listed consumer goods firms in Nigeria. As a result, the ex-post facto research design was adopted in the study. Descriptive analysis was used to summarize the data collated while estimates from Robust Least Square regressions were used to test the hypotheses, which found that Employee Health and Safety Disclosure (EHSD) has a significant but negative effect on return on capital employed of listed consumer goods firms in Nigeria (β = -0.275, p = 0.0000); Pollution Control Disclosure (PCD) has a significant but negative effect on return on capital employed of listed consumer goods firms in Nigeria (β = -0.625, p = 0.0000) and Environmental Remediation Disclosure (ERD) has a significant but negative effect on return on capital employed of listed consumer goods firms in Nigeria (β = -0.141, p = 0.0000). In view of these, the study concluded that as the marketplace becomes more competitive, companies may benefit from adopting a more strategic approach to their environmental communication, emphasizing disclosures that yield positive financial outcomes while efficiently managing the costs associated with those that have adverse effects. The study recommends among others that Human Resources (HR) departments should prioritize the enhancement of employee health and safety measures. This involves conducting regular assessments and implementing necessary improvements to ensure compliance with health and safety regulations, thereby minimizing potential negative impacts on financial performance.
Keywords: Eco-Environmental Cost; Employee Health and Safety Disclosure; Environmental Remediation Disclosure; Performance; Pollution Control Disclosure; Return on Capital Employed